How to Make EU Tourism Sector Greener, more Efficient and Sustainable: A Bibliometric Analysis - Ani Trstenjak; Ivana Tomas Žiković; Saša Žiković (International Journal of Energy Economics and Policy, 2023)
Even if creating jobs and fostering economic growth are two of the tourist industry's most important roles, preserving its sustainability is a big issue on a global scale. Our research aims to provide a bibliometric analysis of the relevant literature used in the VOSviewer software's examination of the sustainability of the industry. The goal is to evaluate the current status of research on environmental aspects of sustainable tourism development and to pinpoint the key areas, journals, articles, and authors from 1996 to 2021. A total of 337 relevant papers on subjects like the utilization of renewable energy sources, energy efficiency, energy indicators, and sustainability in the tourism industry were analysed in the Scopus database, based on their authors, publication year, geographic location, and number of citations. This study provides helpful information to promote theoretical and practical research in this area by adopting a systematic and visual review of all studies pertinent to the development of sustainable tourism.